Factor Analysis of Net Cash Flow Margin Ratio - Rohanova, Hanna (My University, 2019)
The study object is net cash flow or profit margin ratios within a company. Sometimes it is very difficult to reveal and identify the factors that affect the net cash flow margin. Cash flow ratio within a company is analyzed. The financial ratios taken into account while analyzing the cash flows are described. First-order net cash flow drivers are identified upon comparison of cash flow calculation methods. As a result of the factor analysis, the net cash flow margin factor model is offered. It includes 7 ratios: leverage ratio; cash turnover ratio; common profit margin; net cash flow coverage ratio for all liabilities; net operating cash flow ratio for operating activities; turnover ratio for all assets; profitability ratio for average cash balance. In the course of this study, certain net cash flow margin modeling methods were applied. The net cash flow margin is analyzed on a regression basis, which allowed identifying two of the most influential and statistically significant drivers cash turnover ratio and net operating cash flow ratio for operating activities. In comparison with similar known factor cash flow models, the offered model makes it possible to identify the net cash flow drivers in order to form an efficient mechanism for proper cash flow evaluation and management.
Keywords: cash flow; profit margin; financial performance; factor analysis; кафедра фінансів